ANALISIS KEBUTUHAN PENGEMBANGAN E-LKM BERBASIS STEM PADA MATERI MAKROMOLEKUL - Irfandi, Irfandi; Musdansi, Dwi Putri; Murwindra, Rosa; Chandra, Maya Febriani; Rini, Respito (Educational Insights, 2023)
Students' needs for new innovations in chemistry learning need to be identified by lecturers so that students can be motivated to learn. e-LKM development is one of the innovations that can be carried out to keep up with rapid technological developments. E-LKM will be more complex if integrated with a STEM approach to increase student innovation in learning chemistry. This research used qualitative descriptive research with 10 chemistry education students as research subjects. Data collection was carried out using questionnaires and interviews which were then analyzed descriptively. The research results show that 90% students need technology-based learning tools that can be used independently. The teaching materials needed are also expected to not only provide explanations of the material but also help students solve problems in everyday life